2020
DOI: 10.3389/fonc.2020.01514
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Prognostic Value of IDH Mutations in Korean Patients With Cholangiocarcinoma

Abstract: The molecular profile of cholangiocarcinoma (CC) remains elusive. The prognostic value of isocitrate dehydrogenase (IDH) mutations in CC is controversial, and there have been few relevant studies in Asian populations. In the present study, we investigated the frequency and prognostic significance of IDH mutations in Korean patients with CC. CC specimens were collected from patients who underwent surgical liver resection between 2004 and 2019. Clinical and pathological data were retrospectively reviewed from me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In 2021, a next-generation sequencing study involving 20 common solid tumors (more than 28,000 patients in total) showed that the incidence of IDH1/2 mutation is only 1.3%, and the mutation frequency in lung cancer, colorectal cancer, liver cancer, stomach cancer, and other solid tumors is only 0.5%–3% 20 . The unique solid tumor with IDH1/2 mutation frequency exceeding 5% is cholangiocarcinoma (low incidence) 36 , 37 . In addition, IDH1/2 mutation frequency is also high in rare cancers such as chondrosarcoma (38%–86%), undifferentiated carcinoma of the paranasal sinuses (49%–82%), and angioimmunoblastic T-cell lymphoma (20%–30%) 38 .…”
Section: The Cancer Regulatory Mechanisms Of Idh1mentioning
confidence: 99%
“…In 2021, a next-generation sequencing study involving 20 common solid tumors (more than 28,000 patients in total) showed that the incidence of IDH1/2 mutation is only 1.3%, and the mutation frequency in lung cancer, colorectal cancer, liver cancer, stomach cancer, and other solid tumors is only 0.5%–3% 20 . The unique solid tumor with IDH1/2 mutation frequency exceeding 5% is cholangiocarcinoma (low incidence) 36 , 37 . In addition, IDH1/2 mutation frequency is also high in rare cancers such as chondrosarcoma (38%–86%), undifferentiated carcinoma of the paranasal sinuses (49%–82%), and angioimmunoblastic T-cell lymphoma (20%–30%) 38 .…”
Section: The Cancer Regulatory Mechanisms Of Idh1mentioning
confidence: 99%
“…Correlations between IDH mutations in iCCA and clinical outcome parameters have been inconsistent across different studies, perhaps due to issues of sampling bias, heterogeneity in populations, various clinical stages, and limited specimen numbers. [109][110][111][112][113][114][115] On the other hand, mIDH iCCAs show distinct histological and molecular features. iCCAs can be classified histologically into small duct and large duct subtypes.…”
Section: Clinical and Biological Features Of Midh1 Iccamentioning
confidence: 99%
“…The IDH1 mutation is the substitution of arginine 132 by other amino acids, including R132 H/C/L/S ( Golub, et al, 2019 ). Particularly, R132H and R132C are the most common mutation types, with mutation’s frequency ranging from 4.3% to 33% ( Kim, et al, 2020 ).…”
Section: Isocitrate Dehydrogenase1 Mutation and 2-hydroxyglutarate In...mentioning
confidence: 99%